Traffic Management on The Cikereteg-Pancawati Road in The Caringin District Tourism Area Bogor District - Mansyur, Umar; Djakapermana, Ruchyat Deni; Syahbandar, M. Yogie; Rahmawan, Eko Arif (Syntax Corporation, 2024)
Traffic as part of transportation planning is a vital indicator of tourism development. Bogor Regency is one of the favorite tourist destinations in Jabodetabek. One of the tourist attractions in Bogor Regency is natural tourism around the Puncak Bogor area. This study aims to analyze land use around Jalan Cikereteg-Pancawati, analyze the performance and level of traffic service on the road, and conduct a SWOT analysis for traffic management strategies. The study used GIS to analyze changes in land use and analyzed the level of road service on Jalan Cikereteg-Pancawati. The traffic performance analysis was conducted by analyzing the volume values and degrees of saturation on Sundays and Thursdays. The land use analysis showed that the area is dominated by forests, plantations, and rice fields, indicating great potential as a tourist area. The traffic performance analysis revealed that Sundays have higher volume values and degrees of saturation than Thursdays, with the highest degree of saturation occurring on Sunday segment 3. The study concludes that the traffic management strategy for Jalan Cikereteg-Pancawati should focus on managing pavement repairs and road widening, providing bus and car parking, and utilizing available human resources and supporting regulations for the development of Bogor Regency as a natural tourism area. The study's findings suggest that effective traffic management is crucial for the sustainable development of natural tourism in Bogor Regency. The proposed traffic management strategies can help alleviate traffic congestion and improve the overall tourist experience, ultimately contributing to the region's economic growth and social well-being.